2007
DOI: 10.1089/cap.2007.0060
|View full text |Cite
|
Sign up to set email alerts
|

Parent versus Teacher Ratings of Attention-Deficit/Hyperactivity Disorder Symptoms in the Preschoolers with Attention-Deficit/Hyperactivity Disorder Treatment Study (PATS)

Abstract: Results provide important data regarding base rates and concordance rates in this age group and support the hypothesis that preschool-aged children at risk for ADHD exhibit significant differences in behavior patterns across settings. Obtaining ratings from multiple informants is therefore considered critical for obtaining a full picture of young children's functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
61
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 34 publications
16
61
1
4
Order By: Relevance
“…Across all observed differences, parents rated children as more symptomatic than teachers. This finding is consistent with recent research (Gomez, 2007;Malhi et al, 2008, Murray et al, 2007Rettew et al, 2011;Sollie et al, 2012). One possible explanation for this pattern may be referral bias.…”
Section: Pattern Of Parent-rated and Teacher-rated Symptoms Of Adhdsupporting
confidence: 93%
See 2 more Smart Citations
“…Across all observed differences, parents rated children as more symptomatic than teachers. This finding is consistent with recent research (Gomez, 2007;Malhi et al, 2008, Murray et al, 2007Rettew et al, 2011;Sollie et al, 2012). One possible explanation for this pattern may be referral bias.…”
Section: Pattern Of Parent-rated and Teacher-rated Symptoms Of Adhdsupporting
confidence: 93%
“…Amador-Campos et al (2006) reported kappa values of 0.24 for inattentive, 0.21 for hyperactive/impulsive, and 0.25 for combined symptoms. Murray et al (2007) demonstrated that the diagnostic concordance for preschool children "at risk" of ADHD ranged between ĸ = 0.24 and ĸ = 0.26 for the inattentive and hyperactive/impulsive subtypes respectively. Relative to the abovementioned, Malhi et al (2008) indicative of slight to moderate parent-teacher agreement in assigning subtypes of ADHD.…”
Section: Informant Discrepancies In the Assessment Of Adhd Subtypesmentioning
confidence: 99%
See 1 more Smart Citation
“…Em primeiro lugar, as correlações reduzidas a modestas encontradas nos vários estudos apontam para um grau de acordo relativamente baixo entre informadores com papéis diferentes na vida da criança (pais e professores) Cranes et al, 2011;Culp et al, 2001;Gagnon et al, 1992;Gagnon et al, 2007;Goodman, 2001;Gross et al, 2004;Hinshaw et al, 1992;Klyce et al, 2011;Liu et al, 2011;Miner & Clarke-Stewart, 2008;Murray et al, 2007;Phillips & Lonigan, 2010;Renk & Phares, 2004;Stefan, Balaj, Porumb, Albu, & Miclea, 2009;Stone, Otten, Engels, Vermulst, & Janssens, 2010;Verhulst & Akkerhuis, 1989;Vitaro et al, 1991;Winsler & Wallace, 2002). Em segundo lugar, os pais (em especial a mãe) tendem a cotar os seus filhos com mais problemas de comportamento do que os professores (Cranes et al, 2011;Culp et al, 2001;Gagnon et al, 1992;Gross et al, 2004;Herrera & Little, 2005;Miner & Clarke-Stewart, 2008;Verhulst & Akkerhuis, 1989;Winsler & Wallace, 2002).…”
Section: Resultsunclassified
“…Esta ideia da recolha de informação junto de múltiplos informadores tem subjacente a importância das diferentes perspetivas de cada um deles, na tentativa de integrar essa informação para obter um retrato mais coerente/fidedigno do funcionamento da criança, ao interagir com vários adultos com um papel significativo na sua vida e nos diversos contextos em que passa a maior parte do seu tempo (casa e jardim-de-infância) Gagnon, Nagle, & Nickerson, 2007;Murray et al, 2007;Offord et al, 1996;Verhulst & Akkerhuis, 1989).…”
unclassified